Post-training breakdown: acute effects of different training types on body hydration status and performance - Erkan Demirkan; Mehmet İsmail Tosun; Abdurrahim Kaplan; Mert Ayrancı; Damian George Cosmin; Mustafa Arıcı; Mehmet Kutlu; Veysi Aslan; Michael Favre (Frontiers in Psychology)
ObjectiveWrestling is a complex sport that requires a combination of strength, endurance, and wrestling-specific technical training. Endurance activities, such as running, are commonly performed for rapid weight reduction before competition. However, these activities can severely disrupt recovery and lead to significant declines in performance. This study aimed to examine the acute effects of endurance, strength, and wrestling training sessions on hydration status and performance parameters in young wrestlers, providing insights to guide more effective hydration and recovery strategies.MethodA total of 14 experienced young wrestlers participated in a crossover design, completing endurance, strength, and wrestling training sessions on separate days. The hydration status was assessed through urine specific gravity (USG) before and after each session. The performance measures included hand grip strength, back and leg strength tests, anaerobic power (vertical and horizontal jumps), respiratory muscle strength (maximal inspiratory pressure, MIP), and reaction time assessments.ResultsThe endurance training caused the most significant acute reductions in the hydration (USG increase: 0.016 ± 0.005 g/cm3, p < 0.05) and body mass (BM; −1.89 ± 0.4%, p < 0.05), along with immediate performance decrements in the back strength (−7.02 ± 1.2%, p < 0.001), right-hand grip strength (−8.79 ± 2.1%, p < 0.001), jump height (−7.26 ± 1.8%, p < 0.001), and MIP (−9.01 ± 2.3%, p < 0.001). The hydration levels in the endurance group did not fully recover by the next day (USG post-training vs. before the next day’s training: p < 0.05). In contrast, the strength training improved the reaction time before the next day’s session (+5.6 ± 1.3%, p < 0.05), while the attention remained unaffected across all training types.ConclusionEndurance training—commonly used for rapid weight loss—can acutely compromise hydration and reduce key performance measures, with recovery taking more time compared to strength or wrestling sessions. Given these findings, endurance sessions should be strategically scheduled before rest days or low-intensity technical training to minimize their negative effects on subsequent performance. Implementing enhanced hydration strategies during endurance-focused sessions may also help mitigate these acute impacts and optimize recovery and performance in young wrestlers.